Digital Shopping Behavior of Clients: Evidence from Nepalese Youths - Lamichhane, Basu Dev; Lama, Padam Bahadur; Rai, Kussum; Karki, Namrata (Victoria Journal of Management, 2025)
Digital shopping in the recent era has evolved throughout the national and international markets facilitating convenience purchases for customers. However, the complexities are revealed with digital shopping mechanisms. As numerous challenges exist with online shopping, there has been tremendous focus on investigating existing difficulties associated with online shopping. This research examines the impact of privacy and security, product features, and delivery service on digital shopping behavior in Nepalese Youth. It addresses the gap in the literature regarding inconsistent findings. Employing quantitative research design and deductive reasoning, a cross-sectional study was conducted to gather data on individuals’ online purchasing intentions. A convenience sampling method was used, with a sample size of 129 selected from a population of 2500, determined using a sample size calculator at a 98% confidence level and a ±10% margin of error. Of 170 questionnaires distributed, 140 were valid. Descriptive and correlational research designs were employed to explore consumers’ behaviors and attitudes, while causal analysis assessed the impact of perceived risks on purchasing intentions, with age group differences also considered. The study found that privacy, security, and delivery service negatively affect digital shopping behavior, while product features have a slightly positive impact. These findings are valuable for enhancing online retail strategies and improving consumer satisfaction. The study examines the risk factors affecting digital shopping behavior among Tokha Municipality, Kathmandu residents. It focuses on privacy and security, product features, and delivery service. The findings show that different age groups perceive digital shopping behavior differently. Privacy and security are significant, with customers worrying about the potential for personal and financial information theft. Delivery service is also a concern, especially with unfamiliar sellers. However, product features have significantly diminished due to improved retailer standards, enhanced product information, and robust consumer protection. The study found an insignificant positive relationship between product features and digital shopping behavior.